2011
DOI: 10.1123/tsp.25.2.144
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Effects on Attention Allocation and Perception of Exertion

Abstract: The aim of the current study was to test the effectiveness of pleasant odors on perception of exertion and attention allocation. A secondary purpose was to employ a placebo-control design and measure perceived smell intensity during task performance; methods that have been overlooked in previous olfaction studies in the sport and exercise domain. Seventy-six college students (35 females, 41 males) were recruited to perform a handgrip task. They were randomly assigned to one of 4 groups: control, placebo, laven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 41 publications
3
35
0
Order By: Relevance
“…However, a later study found no effect of peppermint aroma on the physiological parameters: oxygen consumption, minute ventilation or respiratory exchange ratio during acute exercise [10]. Basevitch et al [11] published data suggesting that any impact on performance measures may be a consequence of the aromas effect on psychological rather than physiological variables. This contention is further supported by a study that reported decreased anxiety levels and improved performance (accuracy and consistency) on a dart throwing task for participants in a peppermint aroma condition [12].…”
mentioning
confidence: 99%
“…However, a later study found no effect of peppermint aroma on the physiological parameters: oxygen consumption, minute ventilation or respiratory exchange ratio during acute exercise [10]. Basevitch et al [11] published data suggesting that any impact on performance measures may be a consequence of the aromas effect on psychological rather than physiological variables. This contention is further supported by a study that reported decreased anxiety levels and improved performance (accuracy and consistency) on a dart throwing task for participants in a peppermint aroma condition [12].…”
mentioning
confidence: 99%
“…There is general agreement about the importance of studying how different attentional 3 strategies influence performance in sport and exercise settings (Basevitch et al, 2011; 4 Blanchfield, Hardy, de Morree, Staiano, & Marcora, 2014;Connolly & Tenenbaum, 2010; 5 Hutchinson & Razon et al, 2010; for a review, see Brick, MacIntyre, & 6 Campbell 2014). In this regard, previous research has shown that one's ability to self-regulate 7 attentional focus (e.g., attentional flexibility) is associated with the ability to sustain exertive 8 effort in endurance tasks (for a review, see Tenenbaum, 2005).…”
mentioning
confidence: 99%
“…The testing room was the same for all participants, and they all underwent the exact same procedure. Peppermint and lavender odors were selected given their opposite effects on attentional state (Barker et al, 2003;Basevitch et al, 2011;Ho & Spence, 2005;Ilmberger et al, 2001;Moss et al, 2003). "De Tuinen" pure essential oils (De Tuinen Aromatherapie) of peppermint and lavender were used to generate the ambient aromas.…”
Section: Procedures and Designmentioning
confidence: 99%
“…The stimulating aroma peppermint is supposed to increase arousal and induce a more focused attentional state, while lavender, a calming olfactory fragrance, is considered to induce relaxation and a broader attentional state (Barker et al, 2003;Basevitch et al, 2011;Ho & Spence, 2005;Ilmberger et al, 2001;Moss, Cook, Wesnes, & Duckett, 2003). Previous studies have looked into the allocation of attention in space, assuming (and showing) that a more focused or distributed state is associated with a smaller and broader spatial focus of attention, respectively (Dale & Arnell, 2010).…”
Section: Introductionmentioning
confidence: 99%